2020
DOI: 10.1101/2020.05.19.104794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidative Stress and Neuroinflammation in a Rat Model of Co-Morbid Obesity and Psychogenic Stress

Abstract: Contributions: JMS, wrote manuscript, performed Western blot experiments and analyses; JDV, design and performed behavioral experiments, wrote manuscript; YAT, performed Western blot experiments; POA, performed and analyzed ELISA experiments, prepared illustrations, wrote manuscript; JBL, analyzed behavioral data; AYCG and EAB, performed Western blots; DZO and CAC, peformed Western blot analyses; JDF, planned experiments, analyzed data, wrote manuscript. AbstractBackground: There is growing recognition for a r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Recent work from our lab has focused on identifying early (mal)adaptive responses to obesogenic environments [ 18 , 44 , 48 , 49 , 61 ]. Having demonstrated that exposure to an obesogenic diet during adolescence alters the neural and behavioral substrates implicated with emotional regulation, we asked whether these impairments can be attenuated by administering neuregulin-1 (NRG1), a neurotrophic factor with potent neuroprotective and anti-inflammatory properties [ 38 , 41 , 45 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work from our lab has focused on identifying early (mal)adaptive responses to obesogenic environments [ 18 , 44 , 48 , 49 , 61 ]. Having demonstrated that exposure to an obesogenic diet during adolescence alters the neural and behavioral substrates implicated with emotional regulation, we asked whether these impairments can be attenuated by administering neuregulin-1 (NRG1), a neurotrophic factor with potent neuroprotective and anti-inflammatory properties [ 38 , 41 , 45 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a fundamental goal of our investigations is to understand precisely how previous experiences alter behavior. Specifically, we are interested in understanding how adolescent dietary obesity influences stress reactivity [ 18 , 44 , 48 , 49 ]. Thus, in our battery, we have used foot shocks not only to promote fear conditioning but also as a stressor [ 44 , 48 , 49 ], as has been reported by others [ 50 52 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work from our lab has focused on identifying early (mal)adaptive responses to obesogenic environments (Kalyan-Masih et al, 2016; Vega-Torres et al, 2018, 2019a, 2020b; Santana et al, 2021). Having demonstrated that exposure to an obesogenic diet during adolescence alters the neural and behavioral substrates implicated with emotional regulation, we asked whether these impairments can be attenuated by administering neuregulin-1 (NRG1), a neurotrophic factor with potent neuroprotective and anti-inflammatory properties (Li et al, 2012; Depboylu et al, 2015; Guan et al, 2015; Simmons et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Obesity and the dietary intake of saturated fats and simple sugars have emerged as risk factors for the development of anxiety and stress-related disorders (Scott et al, 2008; Perkonigg et al, 2009; Johannessen and Berntsen, 2013; Maguen et al, 2013; Mitchell et al, 2013; Kubzansky et al, 2014; Bartoli et al, 2015; Smith et al, 2015). Consistent with studies in humans, we reported that diet-induced obesity (DIO) in rats: 1) reduces hippocampal volume (Kalyan-Masih et al, 2016), 2) impairs the maturation of the corticolimbic fear circuits (Vega-Torres et al, 2018), 3) enhances behavioral vulnerabilities to psychosocial stress (Kalyan-Masih et al, 2016; Vega-Torres et al, 2018, 2019b), 4) results in profound fear learning and extinction learning deficits (Vega-Torres et al, 2018, 2019b), even in the absence of an obesogenic phenotype (Vega-Torres et al, 2020a), and 5) leads to alterations in biomarkers implicated in inflammatory responses (Santana et al, 2021).…”
Section: Discussionmentioning
confidence: 99%